KONSEPSI CALON GURU BIOLOGI TENTANG IPA, BELAJAR, DAN MENGAJAR - Rustaman, Nuryani; Widodo, Ari (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2001)
A study for one semester in Teaching learning strategy course was carried out to get the profile of biology student teachers conception about science, learning, and science teaching, as we know that constructivist paradigm in education is not just studied as a theory, but needs to be implemented in real teaching learning processes. A number of Biology education students (n =29) were involved as subjects. Their free essay were used as source and were organized through coding and then recoding using specific program (NUD.IST). It was found that there are five categories for their conception about science (i.e. study about nature, collection of knowledge or concepts, research method, the single truth, to worship their Creator); five categories their conception about learning (i.e. changing process, knowledge improvement, conceptual change, thinking process, interaction with environment); and three catagories for their conception aboutÂ science teaching (i.e. as fasilitating, knowledge transfer, interaction between teacher and students). Most of biology students have more than one conception (two or three), but none of them has a complete conception about science, learning and science teaching.Â Biology student teachers conception about teaching (mostly as knowledge transfer) is paralel with their conception about science (mostly as study about nature) and about learning (mostly as knowledge improvement).Â These findings give implication to their supervisor to pay attention more seriously on the students conception abot science, learning, and teaching. Because the way they teach will be influenced by their conception about those things. One suggestion to handle is by giving the student teachers to express their opinion about those things so that they are aware to other conceptions and in turn they will be aware to accept (and apply) conception based on constructivist reference or paradigm.